Die-punch alignment and its effect on the thinning pattern in the square-shaped deep drawing of aluminium alloy. (2017) - Vairavan, H.; Abdullah, A.B.
This study investigates the pattern of thinning in the square-shaped deep drawing of aluminium alloy by focusing on the die-punch alignment. The thickness measurements of the drawn blank are obtained by analysing the images obtained from the Alicona Infinite System, a commercial 3D non-contact surface measurement system. The thinning pattern is then mapped on the basis of the measurements made on a few locations along the drawn blank cross-sectional profile. Results show that misalignments may cause unbalanced thickness, thus leading to the premature failure of the blank. Furthermore, misalignments also increase the load required for the drawing process.